EVALUASI SISTEM INFORMASI REKAM MEDIS DI RSU PKU MUHAMMADIYAH BANTUL BERDASARKAN PENDEKATAN KEMUDAHAN DAN KEMANFAATAN - , PRISSILIA RHESAVANI; , Arief Kurniawan Nur P., SKM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
RSU PKU Muhammadiyah Bantul has changed its Hospital Management Information System for three times since 1998, includes Medical Record Information System, the last update was in August 2012. The goals of this change are to gain the fastest service and responsibility in making reports. As every change will influence the user, it is needed an evaluation to know the userâs acceptance based on perceive ease of use and perceive usefulness. This evaluation will be useful in making decision in the future. This research is a descriptive and qualitative research. The project of this research is cross-sectional and the data are collected by observing and interviewing. Medical Record Information System in RSU PKU Muhammadiyah Bantul is easy to use because it has completed the three indicators of perceived ease of use introduced by Davis (1989), they are easy to learn, improving skill, and easy to operate. It hasnât fulfill the userâs desire because of the items availability and their position. In addition, Medical Record Information System is useful because it has completed five dimensions of perceived usefulness introduced by Chin and Todd (1995), they are making job easier, useful, increasing productivity, enhancing effectiveness, and improving job performance. Yet, it hasnât made reporting activity easier because the statistic data processing such as making BTO, GDR, and NDR canât be done using it.